1999
DOI: 10.1074/jbc.274.16.10693
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide-induced Cooperative Folding of an Intrinsically Unfolded Transcription-activating Fragment of Human Glucocorticoid Receptor

Abstract: A number of biologically important proteins or protein domains identified recently are fully or partially unstructured (unfolded). Methods that allow studies of the propensity of such proteins to fold naturally are valuable. The traditional biophysical approaches using alcohols to drive ␣-helix formation raise serious questions of the relevance of alcohol-induced structure to the biologically important conformations. Recently we illustrated the extraordinary capability of the naturally occurring solute, trimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
141
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(155 citation statements)
references
References 31 publications
14
141
0
Order By: Relevance
“…The primary amino acid sequences of the NTDs of the steroid receptors, which contain transactivation function region AF1, are much less conserved than are DBD and ligand binding domain regions, and several studies have shown that the isolated NTDs are not fully structured in aqueous solution (17,18,27,28). Although the isolated NTDs of steroid receptors have poor sequence homology, in solution they share the characteristic of disordered structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary amino acid sequences of the NTDs of the steroid receptors, which contain transactivation function region AF1, are much less conserved than are DBD and ligand binding domain regions, and several studies have shown that the isolated NTDs are not fully structured in aqueous solution (17,18,27,28). Although the isolated NTDs of steroid receptors have poor sequence homology, in solution they share the characteristic of disordered structure.…”
Section: Discussionmentioning
confidence: 99%
“…The GR AF1 sequence resembles those of acidic transactivation domains of several transcription factors (15,16). When expressed independently, the GR AF1 shows little structure and seems to exist as an ensemble of largely unstructured conformers (17,18). The GR AF1 is known to interact with other transcription factors, and conditional folding has been suggested to be the key for these interactions (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Analysis of the predicted order and disorder composition of the AR NH 2 -terminal domain using the PONDR Protein Disorder Predictor 3 indicates that the FXXLF motif and the AR NH 2 -terminal conserved motif form short structurally ordered regions as indicated by PONDR scores of Ͻ0.1. Each motif is predicted to form an amphipathic ␣-helix, indicating the presence of short structured segments in an NH 2 -terminal region that is otherwise predicted to be largely unstructured.…”
Section: Identification Of An Ar Nh 2 -Terminal Conserved Motif-mentioning
confidence: 99%
“…11 Explanations on the molecular level for these phenomena are only beginning to surface. [12][13][14][15][16][17][18][19] To investigate into the molecular mechanism of these effects by computational methods such as molecular dynamics (MD) simulation techniques, a force field for mixed solvents composed of water and N-oxide species is required that is also compatible with available biopolymer potential energy functions. Noto et al 20 were the first who constructed a force field for a rigid TMAO model in the presence of an aqueous environment based on quantum-chemical calculations of TMAO and a single water molecule within the Hartree-Fock (HF) approximation.…”
Section: Introductionmentioning
confidence: 99%